Combined treatment using Mohs' paste and neoadjuvant chemotherapy for giant gluteal soft tissue sarcoma with malignant fungating wound: a case report. Issue 5 (9th May 2019) - Nemoto, Kazuaki; Okamoto, Masanori; Kito, Munehisa; Aoki, Kaoru; Suzuki, Shuichiro; Takazawa, Akira; Yoshimura, Yasuo; Kato, Hiroyuki
Abstract: A malignant fungating wound is a cutaneous infiltration of malignant tumor or metastatic lesion that develop into ulceration. Local control is often difficult to obtain, because the Quality of Life of patients can decrease considerably due to bleeding, exudation, odor and pain from the wound. There are few studies in the literature that report the use of Mohs' paste for soft tissue sarcoma with malignant fungating wound. We report a case resulting in good local control for a patient with dedifferentiated liposarcoma with gluteal ulceration by the combined use of Mohs' paste and chemotherapy as a pre-operative adjuvant therapy. Mohs' paste controlled the infection, odor and exudation in approximately 2 weeks, and good visualization of the surgical field was obtained due to tumor volume reduction. We found that Mohs' paste is effective as a neoadjuvant therapy for disintegrated soft tissue sarcoma.